A rare case of Amyand's hernia with acute appendicitis in a middle aged man: a case report in Nakhon Phanom Hospital - Khamloy, Khriangsak (Journal of the Association of General Surgeons of Thailand under the Royal of Patronage of HM the King, 2025)
Introduction: Amyand's hernia is a form of inguinal hernia which is consider as extremely rare and this type of hernia occurred up to 1% of all inguinal hernia cases. In this type of inguinal hernia, the content of hernia sac is appendix. Most patient with Amyand's hernia often remains asymptomatic and diagnosed intraoperatively. The diagnosis is challenging, since needs a high index of suspicion and imaging is essential. Surgery is the gold standard of treatment. We report a case of Amyand's hernia that was managed operatively in a public hospital, Thailand . Case Presentation: The patient was a 46-year-old man with a history of intermittent pain in the right inguinal area is seen at the emergency department. He developed right painful inguinal mass. There was no history of abdominal pain and vomiting. Laboratory parameters were leukocytosis and normal film x-rays abdomen series. So, with a diagnosis of right sided partially reducible, incomplete, and indirect inguinal hernia, patient was operated for open hernia repair surgery, intra operatively we found mild inflamed appendix into the inguinal canal. Therefor, we decided to perform hernioplasty (The Bassini endogenous tissue repair technique )and appendectomy. Clinical Discussion: Amyand's hernia is very uncommon and characterized by the presence of the appendix in the hernia sac and it is 0.4–1% of all inguinal hernia cases, some reviews also showed that incidence of Amyand's hernia is extremely rare ,whereas only less than 0.9 % cases complicate into acute appendicitis due to late presentation and missed diagnosis. Conclusion: Amyand's hernia was found only a small proportion of most inguinal hernia cases, and its diagnosis is usually based on incidental finding intra-operatively with an inflamed appendix. This condition may remain asymptomatic inguinal hernia. Mainstay treatment of this type of hernia should be individualized according to appendix's inflammation stage, presence of abdominal sepsis and co-morbidity. Open and Laparoscopy approach for dealing Amyand's hernia are both diagnostic and therapeutic.